INTEGRITAS KONTEKSTUAL REFORMASI ISLAM: TELAAH PEMIKIRAN FIKIH DAN FILSAFAT FAZLUR RAHMAN - Fippy Hidayati; Siti Nurhalisa; Luthfiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine the relationship between the historical-hermeneutic approach, Karl Polanyi's dual-movement theory, and the relevance of moral philosophy and Islamic law in responding to the challenges of modernity, with a special focus on the reformist thought of Fazlur Rahman. The problems raised are the stagnation of Islamic thought due to the dominance of taqlid, the lack of a contextual approach, and the disconnection of the ethical dimension in the application of Islamic law in the era of globalization. This research uses a qualitative method with a descriptive-analytical approach and library research, to explore the main concepts and thoughts of the characters through text analysis and synthesis of ideas. The results of the study show that the historical-hermeneutic approach is able to open up the space for understanding religious texts in a contextual and reflective manner, the theory of dual movements provides a framework for analysis of socio-economic dynamics in Islamic history, and Islamic moral philosophy is an important foundation in maintaining the relevance of Islamic law. Meanwhile, Fazlur Rahman's thinking offers solutions through the renewal of ijtihad, a holistic understanding of the Qur'an, and the strengthening of the ethical dimension in Islamic law. These findings affirm the importance of integration between historical contexts, ethics, and rationality in building responsive and transformative Islamic thought in the modern era.